(untitled) (Semiárida, 2020)
Improvement of the reproductive efficiency of beef livestock herds in Rio Grande do Sul can be achieved either by reducing the age at first breeding of 30-36 months to 18-24 months as well as by increase of average pregnancy rate in the state. The aim of this study was to evaluate the pregnancy rate of beef heifers reared on natural grasslands under rotational grazing in Rio Grande do Sul. The treatments were two rest intervals between grazing, determined by the thermal sums of 375 and 750 degree-days (DD). Heifers used were of the Angus breed starting the experiment at 12 months of age. During the spring/summer, stocking rate was regulated for disappearing of 70% of grasses leaf blade. In autumn/winter stocking rate was fixed and the animals were supplemented daily with corn (0.5% of live weight). At two years of age, heifers of both treatments were bred for 60 days and were maintained on natural grassland under continuous grazing. Pregnancy diagnosis was performed 60 days after the breeding season. Heifers managed during rearing on 375 DD treatment had lower pregnancy rate (75%) when compared with those managed at 750 DD grazing intervals (100%) (P = 0.0001).The average pregnancy rate for both treatments was 85.71%. Treatment 750 DD, during rearing, provides best pregnancy rates. Average pregnancy rates were according to standards of intensive livestock for this category.